Epistemologi dalam islam: Memahami cara berfikir irfani dan sumber-sumbernya - Sha'af, Mohammad Adnan (Maliki Interdisciplinary Journal, 2025)
This article examines epistemology in Islam, especially the irfani way of thinking and its sources, and its relevance in facing the challenges of generation Z. Generation Z, shaped by digital technology, has different thinking and moral characteristics compared to the millennial generation. In this context, irfani knowledge, which emphasizes spiritual experience and intuition, offers an alternative approach that complements the more common rational way of thinking. This article discusses three models of thinking in Islam: bayani, irfani, and burhani, where the main focus lies on irfani as a deep approach in understanding the truth through inner experience, intuition, and spiritual illumination. By integrating the irfani method in learning, teachers are expected to be able to attract attention and understand the unique characteristics of students, thereby increasing effectiveness in education. The author also suggests the need for further research on the irfani method to enrich its understanding and application in the context of Islamic education.